Tingkat Pengetahuan, Sikap dan Perilaku Petani dalam Pengelolaan Konservasi Musuh Alami sebagai Upaya Pengendalian Tungro di Kalimantan Selatan - Elisurya Ibrahim; Diah Arina Fahmi; Yayan Suryana (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2018)
Ibrahim et al, 2018. Level of Knowledge, Attitude and Behavior of Farmers in Managing Conservation of Natural Enemies as Tungro Control Efforts in South Kalimantan. JLSO 7(2):121-127.Â Efforts to secure and maintain food self-sufficiency, especially rice that has been achieved by the government, need to be done. One of them is by controlling plant pests and diseases.Another effort that can be done is to utilize the potential of suboptimal land such as swamps, in addition to optimizing irrigated and rainfed rice fields.Tungro is an important disease that can be threaten rice productivity. Conservation of natural enemies as one method of tungro control needs to be studied at the farmer level. Thepurposes of this study were to examine the level of knowledge, attitudes and behavior of farmers in the conservation management of natural enemies in swamps. This research was conducted at Guntung Ujung, Banjar District South Kalimantan on August 2017.Site selection was carried out by purposive sampling because the location was one of the tungro endemic areas in 2014. The primary data were collected using interviews on 37 respondents farmers, while secondary data was obtained from relevant agencies.Data were analyzed descriptively by scoring.The results showed that the level of knowledge of farmers on the management of conservation of natural enemies belonged to the medium category (64.13%), as well as the attitude of farmers towards the management of conservation of natural enemies was grouped to the medium category (65.77%). The behavior of farmers in supporting the management of conservation of natural enemies was belonged to the medium category (53.67%).